Developing a virtual reality game-based learning media on the immune system for high school students - Baiq Hana Susanti; Muhamad Reihan Amar; Ridhwan Dery Iradat (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The existing literature confirms the cognitive benefits of virtual reality (VR) yet also emphasizes these practical challenges, particularly the demand for applications that are rigorously validated while balancing conceptual understanding, student engagement, and user comfort. This study aims to develop and validate an immersive virtual reality learning resource on the immune system as an effective educational tool. The media was designed on an Android-based game platform and developed using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). Validation was carried out by two media specialists and two subject matter experts, while a small-scale trial involved 19 grade XI students and one biology teacher at SMA 1 Cengkareng. The media validation score reached 97.5%, and the material validation result was 86.3%. Despite minor concerns regarding motion sickness and comfort, both teacher and student responses were positive, scoring 86.79% and 87.16%, respectively. These findings indicate that the developed media is feasible and appropriate to be utilised as an educational aid in biology learning.